2013
DOI: 10.1097/jto.0b013e3182829e2c
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Outcome for Patients with Esophageal Squamous Cell Carcinoma Underwent Surgical Resection Alone: Evaluation of the Seventh Edition of the American Joint Committee on Cancer Staging System for Esophageal Squamous Cell Carcinoma

Abstract: The seventh edition of the AJCC staging system for ESCC is acceptable in predicting survival. However, tumor location does not influence survival in our study. Subdivisions of pT1N0M0 cancers and the N-classification may need to be modified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 23 publications
5
50
0
Order By: Relevance
“…pT category was another independent prognostic factor for early ESCC in our study group, which was similar to those of many previous studies (Endo et al, 2000;Stein et al, 2005;Wijnhoven et al, 2007;Gertler et al, 2011). Previous studies recommended that T1 stage should be subdivided according to the depths of infiltration rather than the histologic grade (Gertler et al, 2011), and we have confirmed this in our previous report (Chen et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…pT category was another independent prognostic factor for early ESCC in our study group, which was similar to those of many previous studies (Endo et al, 2000;Stein et al, 2005;Wijnhoven et al, 2007;Gertler et al, 2011). Previous studies recommended that T1 stage should be subdivided according to the depths of infiltration rather than the histologic grade (Gertler et al, 2011), and we have confirmed this in our previous report (Chen et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…In line with previous study (16), we found that T1a patients (85.7%) had a higher 3-year survival rate than T1b patients (78.4%). This could be due to the different risk of nodes metastases in pT1a and pT1b tumors (0-1.8% vs. 17.5-21%) (16,17). Our results demonstrated that significant discrepancy of 3-year survival were seen among T3 (54.4%), T4a (39.1%) and T4b (18.5%).…”
Section: Discussionmentioning
confidence: 52%
“…In previous studies, lymph node metastasis has been reported to be an important prognostic factor in patients with ESCC [21], [22]. Therefore, the correlation between lymph node metastasis and ESCC patient prognosis was also investigated in this study.…”
Section: Resultsmentioning
confidence: 95%